MENGOPTIMALKAN KINERJA BISNIS ES TEH MANIS SOLO MELALUI PENDEKATAN EKONOMI MANAJERIAL - Bagus Oktavian; Andre Satrio Trihantono, Achmad Yasril, Paduloh (CV. Adiba Aisha Amira, 2024)
The Solo Sweet Tea iced drink business, which has been operating since 2019, aims to provide more job opportunities for the community. This study collects information about the business through observation methods. The research results show that Iced Teh Manis Solo focuses on selling drinks without providing complementary foods. The main product is tea with various flavors that have a strong aroma and sweet taste. The findings of this study reveal that every day Solo Sweet Tea ice requires 75 tea bags, 15 liters of water, 1500 grams of sugar, and 20 kg of ice cubes, which can vary according to customer demand. By applying managerial economic principles, Es Teh Manis Solo can optimize operations and develop its business. For example, they can increase sales through the right marketing strategies and reduce production costs by optimizing the supply chain. Apart from that, the application of risk management can also help these companies overcome challenges such as fluctuating raw material prices and increasingly fierce competition in the beverage market.